Answer:
(f + g)(x) = 3x² + (7/3)x - 8
Step-by-step explanation:
To find (f + g)(x), you need to add both the f(x) and g(x) equations together.
f(x) = x/3 - 2 ..... which is equal to ... f(x) = (1/3)x - 2
g(x) = 3x² + 2x - 6
(f + g)(x) = ((1/3)x - 2) + (3x² + 2x - 6) <----- Add both equations
(f + g)(x) = 3x² + (1/3)x + 2x - 2 - 6 <----- Rearrange (2 = 6/3)
(f + g)(x) = 3x² + (7/3)x - 8 <----- Simplify similar terms
Answer:
50
Step-by-step explanation:
4 x 10 = 40 and 2 x 5 = 10 so add them together
Answer:
This is an a fake answer but I want to supposed to be multiple pictures?? Because you said add an explanation for each picture and is this history? Are you sure it’s math
Step-by-step explanation:
Answer:
b
Step-by-step explanation:
its closest to -.9 so it has to be that one
The answer to this question might be A